O efeito mediador da regulação emocional na relação entre a expressividade emocional da família de origem e as reacções maternas à expressão de emoções positivas das crianças - Palmeira, Lara (2010)
The fundamental role of the family, especially that of the parents, as the main agents of the socialization of emotions, has been highlighted throughout research. From an early onset, parental practices are a model for the identification and understanding of emotions, for learning the emotional expression and regulation strategies. This study examines the mediaton effect of the strategies for emotion regulation used by mothers of 169 children from 8 to 12 years, in the relation between their recollections of their family-of-origin expressiveness and the way they react to the positive emotional expressiveness of their children. We found evidence for the existence of a transgenerational effect on the process of socialization of emotions, in that the mother’s strategies for emotional regulation work as a mediation effect of the relation between the emotional expressiveness of the mother’s family-of-origin and the maternal reactions to the positive emotional expression of their children.